The foundation of Hope : turning dreams into reality - Elford, R. John (Liverpool Hope University College, 2003)
The Foundation of Hope is both a celebration and an analysis of the creation of Liverpool Hope University College in 1996 and of some of its achievements to date, during an exciting period in British higher education. The central focus is the student experience at Hope University College. Contributors also examine the way that teaching and research in theology have developed over the years and the important community regeneration work Hope University College carries out in various areas of Liverpool.